The Remote Networked School (RNS) Model: An ICT Initiative To Keep Small Rural Schools and Their Local Community Alive - Allaire, Stephane; Bikie, Nadège; Laferrière, Thérèse; Gagnon, Vincent; Hamel, Christine; Labonté-Hubert, Émilie; Deslandes, Rollande (International Journal about Parents in Education, 2023)
The importance of peer interaction for learning purposes is a well-known fact in educational theory, and a school of a small size is particularly challenged to engage same-age students in social exchange of this nature. For almost a decade, an action research partnership (Laferrière & Breuleux, 2002) has been established. A systemic approach was applied (Banathy, 1991; Engeström, 1999; Seidel & Perez, 1994). It has meant tackling an educational challenge and social one as well as distance from urban areas using the support of the Internet. Partners’ objective was to design and study (see design experiment methodology: Brown, 1992; Collins, 1992; 1999), from an ecological perspective (Nardi & O’Day, 1999). The model that was cocreated was meant to enrich interactions for learning purposes in rural schools. More concretely, with the use of information and communication technologies (ICTs), we designed a model whose purpose is to bring classrooms of different schools and regions to work and learn together. This paper focuses on two poles of results of the Remote Networked School (RNS) model: 1) the advantages of collaboration between schools from teachers’ point of view; 2) parents’ social representations of the RNS model and its value as it pertains to their children’s education.